Dynamic Profile of S-Layer Proteins Controls Surface Properties of Emetic Bacillus cereus AH187 Strain - Boutonnet, Cécile; Lyonnais, Sébastien; Alpha-Bazin, Beatrice; Armengaud, Jean; Château, Alice; Duport, Catherine (Frontiers in Microbiology, 2022)
covered by a two-dimensional array of proteinaceous subunits. This surface layers (S-layer) is incompletely characterized for many microorganisms. Here, we studied Bacillus cereus AH187. A genome analysis identified two genes encoding the S-layer proteins SL2 and EA1, which we experimentally confirmed to encode the two protein components of the S-layer covering the surface of B. cereus. Shotgun proteomics analysis indicated that SL2 is the major component of the B. cereus S-layer at the beginning of exponential growth, whereas EA1 becomes more abundant than SL2 during later stages of stationary growth. Microscopy analysis revealed the spatial organization of SL2 and EA1 at the surface of B. cereus to depend on their temporal-dynamics. Our results also show that a mutant strain lacking functional SL2 and EA1 proteins has distinct surface properties compared to its parental strain, in terms of stiffness and hydrophilicity during the stationary growth phase. Surface properties, self-aggregation capacity, and bacterial adhesion were observed to correlate. We conclude that the dynamics of SL2 and EA1 expression is a key determinant of the surface properties of B. cereus AH187, and that the S-layer could contribute to B. cereus survival in starvation conditions.